Overview of Extension Program Planning Models - John M. Diaz; Cody Gusto; David Diehl (EDIS)
The use of program plan development models within Extension has a long history of application based on environmental context, interest, and perceived value. The purpose of this 6-page article is to articulate a comparative overview of the various program planning models designed and employed by Extension professionals in education contexts. Written by John Diaz, Cody Gusto, and David Diehl and published by the UF/IFAS Department of Agricultural Education and Communication, January 2018. http://edis.ifas.ufl.edu/wc289